Improving Students Reading Report Text Skill Through Paired Reading Strategy Grade X SMK Minqu Gumukmas - Laila, Siti Nur; Ghozali, Imam; Sabartono, Ribut (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
This study aims to obtain data on improving reading skills Report text using Paired Reading (PR) class X SMK MINQU Gumukmas technique. Research subjects were students of class X in semester 2. This research was carried out using the Kemmis and Mc models. Taggart implemented with stages planning, implementing, observing, and reflecting. The results of the research using Paired Reading (PR) show the data obtained from the evaluation test in order to improve students' reading of the report text in order to obtain a score ≥ 75 in the pre-test of 39%. In the meantime, the teacher activity monitors and students in the first round of the first meeting were 49 percent and the second round was 60 percent, while the second round of the meeting was 70 percent and the second round was 78%. The Paired Reading Strategy can therefore improve students' reading report on text skills in Class X.